2018
DOI: 10.1088/1361-6560/aabd53
|View full text |Cite
|
Sign up to set email alerts
|

Lesion detectability in 2D-mammography and digital breast tomosynthesis using different targets and observers

Abstract: This work investigates the detection performance of specialist and non-specialist observers for different targets in 2D-mammography and digital breast tomosynthesis (DBT) using the OPTIMAM virtual clinical trials (VCT) Toolbox and a 4-alternative forced choice (4AFC) assessment paradigm. Using 2D-mammography and DBT images of virtual breast phantoms, we compare the detection limits of simple uniform spherical targets and irregular solid masses. Target diameters of 4 mm and 6 mm have been chosen to represent ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 49 publications
(72 reference statements)
2
14
0
Order By: Relevance
“…DBT was found to have a lower threshold detectable mass diameter than 2D-mammography (p-value of < 0.0001), whichever choice of PC was made; 90.7% or 62.5%, although the threshold values are higher for the higher PC choice. The order of performance of the systems agrees with a previous 4AFC observer study [20], carried out using methods similar to those used in the current study, but which used Hologic reconstruction software instead of Briona reconstruction software, and which evaluated the signal contrast needed to correctly identify a mass, instead of the threshold detectable mass diameter. Elangovan et al [20] showed that observers needed over three times the signal contrast to correctly identify a mass in 2D-mammography compared with DBT (narrow angle).…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…DBT was found to have a lower threshold detectable mass diameter than 2D-mammography (p-value of < 0.0001), whichever choice of PC was made; 90.7% or 62.5%, although the threshold values are higher for the higher PC choice. The order of performance of the systems agrees with a previous 4AFC observer study [20], carried out using methods similar to those used in the current study, but which used Hologic reconstruction software instead of Briona reconstruction software, and which evaluated the signal contrast needed to correctly identify a mass, instead of the threshold detectable mass diameter. Elangovan et al [20] showed that observers needed over three times the signal contrast to correctly identify a mass in 2D-mammography compared with DBT (narrow angle).…”
Section: Discussionsupporting
confidence: 84%
“…The order of performance of the systems agrees with a previous 4AFC observer study [20], carried out using methods similar to those used in the current study, but which used Hologic reconstruction software instead of Briona reconstruction software, and which evaluated the signal contrast needed to correctly identify a mass, instead of the threshold detectable mass diameter. Elangovan et al [20] showed that observers needed over three times the signal contrast to correctly identify a mass in 2D-mammography compared with DBT (narrow angle). The work by Mackenzie et al [19] used similar methods to quantify the minimum detectable mass diameter for 2D-mammography and DBT for the Siemens Inspiration system (which has the wide-angle geometry used in this study).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations